Oxidative stress and histological alterations produced by dietary copper in the fresh water bivalve Diplodon chilensis - Sabatini, Sebastian Eduardo (2011)
The aim of this work was to study the oxidative stress effects and histological alterations caused by dietary copper on the filter-feeding freshwater mussel Diplodon chilensis. Bivalves were fed during 6 weeks with the green algae Scenedesmus vacuolatus previously exposed to copper. Metal concentration in algae cultures and bivalve digestive gland was measured by TXRF. A maximum accumulation of 0.49 μg Cu/mg protein was detected at week 6. Also at this week, the hepatosomatic index (HSI) showed the highest decrease (50%) in response to Cu exposure. SOD and GST activities were significantly increased at weeks 4, 5 and 6, reaching an activity on average 50% higher than in controls for GST. CAT activity and GSH increased significantly at weeks 5 and 6. Despite this response, oxidative damage measured as TBARS and carbonyl groups contents increased significantly at weeks 4, 5 and 6, respectively. Digestive tubule and duct atrophy and cell-type replacement in treated mussels were observed by histological studies. The presence of intracellular rhodanine-positive granules, suggests copper accumulation in intracellular vacuoles of digestive cells. © 2011 Elsevier Inc. All rights reserved.